2018
DOI: 10.1136/jnnp-2018-318212
|View full text |Cite
|
Sign up to set email alerts
|

Models for predicting risk of dementia: a systematic review

Abstract: The predictive ability of existing dementia risk models is acceptable. Population-specific dementia risk models are necessary for populations and subpopulations with different characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
159
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(161 citation statements)
references
References 40 publications
2
159
0
Order By: Relevance
“…In future trials, up-to-date scientific evidence on risk factors and prevention should not only be incorporated into the content of the interventions, but also communicated in a pragmatic way, which would allow participants to understand how one can affect his/her own dementia risk. Available dementia risk scores and tools [27,28] could be useful in this regard. Importantly, considering that lack of knowledge could be perceived as a barrier towards behavioural and lifestyle change for dementia prevention [13] and knowledgeable individuals may be more likely to pursue an active and healthy lifestyle [29], promoting awareness among older adults should also be considered a priority for public health policies.…”
Section: Discussionmentioning
confidence: 99%
“…In future trials, up-to-date scientific evidence on risk factors and prevention should not only be incorporated into the content of the interventions, but also communicated in a pragmatic way, which would allow participants to understand how one can affect his/her own dementia risk. Available dementia risk scores and tools [27,28] could be useful in this regard. Importantly, considering that lack of knowledge could be perceived as a barrier towards behavioural and lifestyle change for dementia prevention [13] and knowledgeable individuals may be more likely to pursue an active and healthy lifestyle [29], promoting awareness among older adults should also be considered a priority for public health policies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CAIDE highlights the role of vascular factors which have found to have inverse associations with dementia among older age groups [20][21][22]. Therefore, CAIDE is a good index for mid-life dementia risk prediction [23] but application of it among older adults is limited. However, in the Finnish populationbased CAIDE study, a late-life dementia index has recently been developed by using a supervised machine learning method which is able to handle large amounts of data, structure risk factors into groups and give a comprehensive overview of an individual's predictive profile pointing the most relevant risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our Results showed that modifiable indicators (baseline cognitive function and ADLs), and nonmodifiable factors (age, education and marriage) were strong predictors forecasting CI. Recent metaanalysis [9] of 61 cohort studies regarding the predictive model for risk of dementia summarized common predictive factors used in included studies including demographic factors (age, education and sex), cognitive function, health and lifestyles and genetics. In consistent with this study, we found modifiable factor of cognitive function was valuable to predict dementia but our study was not able to include genetics information.…”
Section: Discussionmentioning
confidence: 99%